The Study of Organic Fertilizers Application on Two Soybean Varieties in Organic Saturated Soil Culture - Aziz, Sandra Arifin; Melati, Maya; Ramadhani, Elrisa (Journal of Tropical Crop Science, 2016)
Indonesia is facing soybean shortage and the low productivity of soybean production from decreasing acreage. Saturated soil culture (SSC) could be one of the solutions for marginal land with drainage problem. Saturated soil culture is cultivation technology that gives continuous irrigation and maintains water depth constantly and makes soil layer in saturated condition. Farmers can use on-farm inputs that are normally available at the production site. An organic farming system may be able to ensure local and regional food security through continuous production. The study was conducted at Cikarawang Experimental Station of Bogor Agricultural University, Indonesia, from December 2009 to February 2011. The objective of the research was to determine the influence of organic fertilizer application on the productivity of two varieties of soybean, “Anjasmoro” and “Wilis”,    in organic saturated soil culture conducted in two cropping seasons. Prior to the experiment all plots were applied with 2 ton.ha-1 of dolomite, 2 ton.ha-1 of rice hull ash, and 10 ton.ha-1 of chicken manure. The experiment of the first season used split plot design with six replications. The main-plot was organic fertilizer that consisted of chicken manure only (20 ton.ha-1), chicken manure (10 t.ha-1) + Centrosema pubescens (4.2 t.ha-1), chicken manure (10 ton.ha-1) + Tithonia diversifolia (4.2 t.ha-1). The sub-plot was soybean varieties “Anjasmoro” and “Wilis”. The soybean productivity was not affected by the application of organic fertilizers. “Willis” productivity (1.98 t.ha-1) was higher than “Anjasmoro” (1.80 t.ha-1). The experiment of second season used split-split plot design with three replications. The main-plot consisted of 50 and 100% fertilizer rate of the first cropping season; the sub-plot was the same types of organic fertilizer with soybean varieties as sub-sub-plot. Rate of fertilizer, types of organic fertilizer and soybean variety did not affect productivity. Application of 50 and 100% rate of fertilizer in the second season produced 2.41 and 2.55 t.ha-1 of dry seeds, respectively. Soybean plants treated with chicken manure, green manure from C. pubescens and T. diversifolia produced 2.45, 2.50 and 2.49 t.ha-1 of dry seeds, respectively. “Anjasmoro” and “Wilis” produced 2.50 and 2.45 t.ha-1 of dry seeds, respectively. Productivity in the second season was 26.26-36.61% higher than those of the first cropping season.